Phytobiont and Ecosystem Restitution (Springer Singapore, 2018)
This book offers present-day retrospectives and future perspectives on 'phytobiont' studies in the context of phyto-micro restitution, filling some of the information gaps in this promising research field. It discusses several ecosystem restitution strategies using dissimilar groups of microbes alone or in association with plants, as well as advances in metagenomics technology for studying in situ micro and macro communities in contaminated soil. It addresses topics such as the status quo, and the perspectives of microbial researchers and scientists, foresters, students, environmentalists, agriculturists and professional engineers. The rising pollution levels caused by xenobiotics is one of the biggest problems of our times, and as such the book comprehensively elaborates the latest research in this field and describes how the issue can be tackled using micro-organisms. With detailed diagrams and illustrations, the book is a valuable resource for experts and novices in the field of microbial bioremediation, phyto-bioremediation and environmental microbiology.